Predictors of Esophageal Varices and Risk of Variceal Bleeding in Patients of Liver Cirrhosis - Panta, Prabesh; Khadka, Dipendra; Basnet, Subhechhya; KC, Rupak; Khanal, Bibek; Shah, Gaurav Jung (Journal of Nepalgunj Medical College, 2022)
Introduction: Variceal bleeding from esophageal varices has high morbidity and mortality. There are invasive and non invasive methods by which risk of bleeding can be predicted. Upper Gastro-intestinal endoscopy is invasive, uncomfortable and expensive procedure though being the gold standard to screen Esophageal Varices (EV).Aims: To know the role of non-invasive markers for prediction of esophageal varices and variceal bleed with liver cirrhosis.Methods: A prospective hospital based study was carried in the Department of Internal Medicine, Nepalgunj Medical College, Kohalpur from October  2021 to March 2022. A total of 70 patients who met the inclusion criteria were enrolled. The non invasive markers were done and correlated with endoscopy.Results: Our study included 70 patients with liver cirrhosis. The mean age in our study was 63.1±8.346 years. During upper gastrointestinal endoscopy, esophageal varices was present in 46 (65.71%) patients. Child Turcot Pugh Score C (81.43%) was found in majority. Significant association was found between score C (P